133k views
1 vote
Simplify each expression by distributing and combining like terms
8(x + 5) - 4(x + 4)

2 Answers

3 votes

Answer:

4x+24

Explanation:

To solve this problem, first you have to use the distributive property of
\displaystyle a(b+c)=ab+ac.

First, expand.

8(x+5)- 4(x+4)

8(x+5)

8*x=8x

8*5=40

8x+40

8x+40- 4(x+4)

-4(x+4)

-4*x=-4x

-4*4=16

-4x-16

8x+40-4x-16

Next, solve.

8x+40-4x-16=4x+24

Therefore, the correct answer is 4x+24.

User Jon McPherson
by
4.6k points
4 votes

Answer:

4x+24

Explanation:

we have: 8(x + 5) - 4(x + 4)

we apply distributive property:

8*x+8*5-4*x-4*4

we have:

8x+40-4x-16

4x+24

User Jean Monet
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.